1981
DOI: 10.3109/00207458108985827
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Longitudinal Effects of the Transcendental Meditation Technique on EEG Power and Coherence

Abstract: EEG alpha coherence and slow alpha power were recorded from frontal and occipital derivations during relaxation or the Transcendental Meditation (TM) technique in fifteen subjects. Subjects were tested before and after a two-week baseline period in which half practiced twice daily relaxation and half did not change their schedule. All subjects were then instructed in the TM technique and retested after a two-week period of twice daily practice of the technique. During the first two-week period there were no gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 7 publications
2
42
1
Order By: Relevance
“…It has been reported that an increase in alpha coherence from the frontal to the central regions is a more sensitive EEG parameter of the meditative state than power or amplitude [8,9]. Findings suggestive of autonomic relaxation during meditation have been widely reported [10,11].…”
Section: Introductionmentioning
confidence: 93%
“…It has been reported that an increase in alpha coherence from the frontal to the central regions is a more sensitive EEG parameter of the meditative state than power or amplitude [8,9]. Findings suggestive of autonomic relaxation during meditation have been widely reported [10,11].…”
Section: Introductionmentioning
confidence: 93%
“…Alertness is indicated by increased electroencephalogram (EEG) coherence during Transcendental Meditation practice; increased integration of brain functioning is also found longitudinally (Dillbeck & Bronson, 1981;Travis et al, 2010;Travis et al, 2009). Additional research, including reduced cortisol during the practice and more effective cortisol response to stress, indicates that the physiological changes during the practice are counter to those found during stress and support recovery from stress (Jevning, Wilson, & Davidson, 1978;MacLean et al, 1997;Walton et al, 2004).…”
Section: Articlementioning
confidence: 99%
“…These studies have shown increased EEG coherence during Transcendental Meditation (e.g. Gaylord et al, 1989;Levine, 1976;Travis and Orme-Johnson, 1989;Travis et al, 2002; experienced practitioners of Transcendental Meditation as well as novices showed increased alpha coherence compared to resting (Dillbeck and Bronson, 1981;Travis, 2001;Travis and Wallace, 1999). Zenmeditation reportedly increased alpha coherence in meditation novices (Murata et al, 2004).…”
Section: Introductionmentioning
confidence: 98%